Carbohydrate improves exercise capacity but does not affect subcellular lipid droplet morphology, AMPK and p53 signalling in human skeletal muscle - Fell, J. M.; Hearris, M. A.; Ellis, D. G.; Moran, J. E. P.; Jevons, E. F. P.; Owens, D. J.; Strauss, J. A.; Cocks, M.; Louis, J. B.; Shepherd, S. O.; Morton, J. P. (The Journal of Physiology, 2021)
Muscle glycogen and intramuscular triglycerides (IMTG, stored in lipid droplets) are important energy substrates during prolonged exercise. Exercise-induced changes in lipid droplet (LD) morphology (i.e. LD size and number) have not yet been studied under nutritional conditions typically adopted by elite endurance athletes, that is, after carbohydrate (CHO) loading and CHO feeding during exercise. We report for the first time that exercise reduces IMTG content in both central and peripheral regions of type I and IIa fibres, reflective of decreased LD number in both fibre types whereas reductions in LD size were exclusive to type I fibres. Additionally, CHO feeding does not alter subcellular IMTG utilisation, LD morphology or muscle glycogen utilisation in type I or IIa/II fibres. In the absence of alterations to muscle fuel selection, CHO feeding does not attenuate cell signalling pathways with regulatory roles in mitochondrial biogenesis.